Being a better version of yourself: genetically engineered probiotic bacteria as host defense enhancers in the control of intestinal pathogens - Ewa Carolak; Joanna Czajkowska; Adrianna Stypułkowska; Wiktoria Waszczuk; Agata Dutkiewicz; Krzysztof Grzymajlo (Gut Microbes)
Intestinal pathogens pose a significant global health burden, and traditional antibiotic treatments often disrupt the beneficial gut microbiota that plays a crucial role in maintaining host health through pathogen prevention and immune regulation. Although probiotics have emerged as promising therapeutic agents, their efficacy is limited by strain-dependent variations, survival challenges in the gastrointestinal tract, and inconsistent immune responses. Recent advances in genetic engineering, particularly CRISPR-Cas systems and their combinations with complementary technologies, such as Cre-lox and RecE/T, have enabled the precise modification of probiotic strains to enhance their therapeutic potential. These enhanced probiotics demonstrate improved functionality through multiple mechanisms, including increased adhesion via the expression of specific proteins (InlA, FnBPA, and LAP), targeted antimicrobial activity through engineered sensing systems (Lactococcus lactis detecting Vibrio cholerae CAI-1), and enhanced immunomodulation through cytokine production. Results have demonstrated the potential of genetically modified probiotics in preventing and treating gastrointestinal infections through mechanisms that include competitive exclusion, bacteriocin production, intestinal barrier reinforcement, and immune modulation. However, challenges remain in ensuring genetic stability and preventing horizontal gene transfer. Future research should focus on optimizing probiotic strains for targeted applications while addressing biosafety concerns. By understanding the complex interplay between probiotics, pathogens, and host immunity, innovative strategies can be developed to harness the full therapeutic potential of probiotic interventions in maintaining gut health.